1985
DOI: 10.1002/chin.198536159
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: REACTION OF DITHIOBIURET WITH α‐ACETYLENIC KETONES

Abstract: Durch Reaktion der Acetylenketone (I), die über eine aktivierte Acetylenfunktion verfügen, mit Dithiobiuret im Molverhältnis 4:1 werden die Bis‐ketovinylsulfide (IIIa) bzw. (IIIb) als E/E‐,E/Z‐ und Z,Z‐Gemische erhalten.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Earlier we reported that the interaction of benzoylacetylene with 2,4-dithiobiurete in MeOH and MeCN is accompanied by elimination of a sulfur atom from the molecule of nucleophilic reagent, leading to the formation of bis(¯-benzoylvinyl)sul¯de [6].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Earlier we reported that the interaction of benzoylacetylene with 2,4-dithiobiurete in MeOH and MeCN is accompanied by elimination of a sulfur atom from the molecule of nucleophilic reagent, leading to the formation of bis(¯-benzoylvinyl)sul¯de [6].…”
Section: Resultsmentioning
confidence: 99%
“…As shown experimentally, these compounds are prone to ring opening, perhaps due to the electrostatic repulsion of large-size sulfur atoms at the methyne carbon atom or to the recyclization to the more stable 1,3,5-triazine (7) and 1,3,5-thiadizine (8). With 2,4-dithiobiurete (2 a) [6] and its mono-substituted analogs (2 b, c; R 2 = H), the presence of one more proton at the terminal nitrogen atom results in the formation of a transition complex (B) and leads to sulfur atom elimination forming (thiocarbamoyl)carbodiimides (D) and/or (thiocarbamoyl)isothiocyanates [7] (Scheme 2).…”
Section: Methodsmentioning
confidence: 94%
See 3 more Smart Citations